Twenty-First-Century Readings of ‘Tender is the Night’ - Blazek, William,Rattray, Laura (Liverpool University Press, 2007)
Bringing together established Fitzgerald scholars from the United Kingdom, Europe and North America, this collection offers eleven new readings of F. Scott Fitzgerald's 1934 novel, Tender is the Night. Contributors include editors of the F. Scott Fitzgerald Review, the general editor of the Cambridge Edition of the Writings of F. Scott Fitzgerald, members of the Fitzgerald Society Executive, and the directors of the biennial F. Scott Fitzgerald conference.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Fitzgerald; F. Scott; Tender is the night